Task phase‐specific involvement of the rat posterior parietal cortex in performance of the TUNL task. (27th May 2020) - Scott, Gavin A.; Cai, Shuang; Song, Yuanyi; Liu, Max C.; Greba, Quentin; Howland, John G.
Abstract: The posterior parietal cortex (PPC) participates in cognitive processes including working memory (WM), sensory evidence accumulation, and perceptually guided decision making. However, surprisingly little work has used temporally precise manipulations to dissect its role in different epochs of behavior taking place over short timespans, such as WM tasks. As a result, a consistent view of the temporally precise role of the PPC in these processes has not been described. In the present study, we investigated the temporally specific role of the PPC in the Trial‐Unique, Nonmatching‐to‐Location (TUNL) task, a touchscreen‐based, visuospatial WM task that relies on the PPC. To disrupt PPC activity in a temporally precise manner, we applied mild intracranial electrical stimulation (ICES). We found that intra‐PPC ICES (100 μA) significantly impaired accuracy in TUNL without significantly altering response latency. Moreover, we found that the impairment was specific to ICES applied during the delay and test phases of TUNL. Consistent with previous reports showing delay‐ and choice‐specific neuronal activity in the PPC, the results provide evidence that the rat PPC is required for maintaining memory representations of stimuli over a delay period as well as for making successful comparisons and choices between test stimuli. In contrast, the PPC appears not to be critical for initial encoding of sample stimuli. This pattern of results may indicate that early encoding of visual stimuli is independent of the PPC or that the PPC becomes engaged only when visual stimuli are spatially complex or involve memory or decision making. Abstract : A, Schematic showing the general progression of a TUNL trial. B, A representation of the interior of a touchscreen chamber used in the experiment. C, A schematic representation of example stimulus distances used in TUNL